ISLAMIC-ECORELIGIOUS: PRINSIP-PRINSIP TEOLOGIS ISLAM TENTANG ETIKA LINGKUNGAN - Fahruddin Faiz (UIN Sunan Kalijaga Yogyakarta, 2014)
Environmental Ethics deal with the moral relationship ofhuman beings with the environment. It answers questions like, why is it wrong for humans to pollute and destroy the environment? Is it wrong to pollute the environment because it harms the present or the future of human well-being or because nature itselfpossesses an innate value? The framework of the behavior of Muslims in respect to nature is a very important component in Islamic ethics. Both the Quran and Hadith (Sunna) emphasize protecting and valuing the environment as a central component of faith. Though Islamic ethics is providing Muslims with very sophisticated and just principles; the majority of Muslims are not taking the forefront in protecting nature and in shaping sustainable policy and practices. The aim in this article is to assess the relationship between nature and Islamic ethics and possible Islamic responses to the environmental crisis.